Acute pediatric neurology - Berweck, Steffen 1968- (Springer, 2014)
This book provides recommendations for evaluation and therapy in the area of acute pediatric neurology; these are presented didactically with frequent use of illustrations and algorithms. Chapters in the first part of the book discuss presenting symptoms of acute neurological conditions. The second part of the book covers major areas of acute pediatric neurology and each of these chapters has three key elements: description of presenting symptoms; recommended assessments; and recommended interventions. Acute Pediatric Neurology provides an accessible, clinically focused guide to assist physicians in the emergency ward or intensive care unit in decisions on diagnosis and therapeutic interventions in all major acute pediatric neurological diseases.